لتحليل smartPLS إشكالية تحديد نوع نموذج القيا س في برنامج - مدخل, خالد; طير, عبد الحق (University of Eloued جامعة الوادي, 2022)
In recent years, interest in partial least squares structural equation modeling (PLS-SEM) has increased. And we can know this method as the second generation of modeling that can be very useful for researchers to complete their various research, This research paper aims to clarify the difference between reflective measurement models and formative measurement models as one of the two options in partial structural equation modeling (PLS-SEM) using smartpls program, which is the latest in this method. Through this study, the researcher can get acquainted well with the reflexive and formative models and establish his works in order to ensure the best model, more important and closer to the concept of his study. Thus this paper gives directions to properly implement smartPLS in this new implementation.
The problem of determining the type of measurement model in the smartPLS data analysis program
مداخلة. الملتقى الدولي الافتراضي حول: البيانات الضخمة والاقتصاد الرقمي كآلية لتحقيق الإقلاع الاقتصادي في الدول النامية "الفرص، التحديات والآفاق"
Keywords: نمذجة المعادلات الهيكلية، نماذج القياس الانعكاسي، نماذج القياس التكويني، smartPLS; Structural Equation Modeling; reflective models; formative models; smartPLS.